Impacto de los parámetros de diseño en la ventilación natural de un ático de una casa familiar de Santa Fe (Argentina) - Berli, Marcelo Eduardo (2022)
The roof of a family home introduces important amounts of heat into the house. In Santa Fe city (Argentina), the attic of social family houses is not designed with thermal optimization purposes. In this work, a low Reynolds number k-eturbulent model is computationally implemented to show that a proper selection of constructive parameters of a ventedattic leads to a great reduction of the heat transferred from the roof to the ceiling. The main physical consequence of avented attic is the existence of a convective flow barrier close to the roof that carries important amounts of heat fromthe attic out to the environment. It is shown that the heat transferred through the ceiling to the interior of the house canbe reduced in more than 70 % for summer conditions. Roof pitch and attic volume are also explored